AB0979 The Distribution of JIA Subtypes and Evaluation of the Disease Status in Turkey. (9th June 2015) - Basbozkurt, G.; Saglam, C.; Fidanci, B.; Barut, K.; Sozeri, B.; Makay, B.; Simsek, D.; Gulhan, B.; Ozden, A.; Gok, F.; Acikel, C.; Ozen, S.; et al.
Abstract : Background: Juvenile idiopathic arthritis (JIA) is the most common chronic rheumatic disease in childhood, affecting the joints and lasting at least 6 weeks, with the age of disease onset under 16 years. The classification of the childhood chronic arthritis hasn't been solved. Objectives: We aimed that analysing the demographics, clinical and laboratory features, disease status, and subtype distributions of JIA according to the International League of Associations for Rheumatology (ILAR) criteria in Turkey. Methods: Between March 2010 and February 2014 with this cross-sectional study, consecutive patients seen with JIA in selected 5 major centres. All patients were classified according to the ILAR criteria. Related to the disease status assessment we evaluate acute phase reactants, physician-patient-parent global assessment of overall disease activity (PGA)(21circle VAS), pain scale (10cm VAS), disease status, and Juvenile Arthritis Damage Index (JADI). We checked the correlations between physician-patient-parent global assessment (PGA) of overall disease activity, and disease status scores. Results: In this study, 208 (58.1%) females and 150 (41.9%) males were evaluated (Female/Male:1.39). The mean age of patients was 11.15±4.47 years. The distributions of JIA patients according to onset of disease were as follows: systemic 50 (13.9%), oligoarticular extended 35 (9.4%), oligoarticular persistent 104 (29%), rheumatoid factor (RF) positive polyarthritis 5 (1.2%), RF negative polyarthritis 89 (24.9%), enthesitis-related 51 (13.8%), psoriatic 15 (3.8%), unclassified group 9 (2.6%). The frequency of uveitis was 21 (15.1%) among all of the oligoarticular patients and 12 (5.5%) among in the other group. ANA was positive mainly among the oligoarticular onset patients. 16 patients also had FMF. Among systemic JIA patients, the frequency of macrophage activation syndrome was 24% (n=12). Related to the disease status of the subtypes of JIA revealed that while the RF positive polyarthritis was found to have the highest, and the unclassified group has the lowest activity score via using Articular JADI. The RF (-) polyarthritis was found to has the highest, and the unclassified group has the lowest activity score according to the Extra-articular JADI. Based on the last week's parent-patient-pain score, while the unclassified group has the highest, the psoriatic arthritis has the lowest activity score. Assessment of the disease status by the PGA was resulted the fact that there was statistically significant positive correlation between parent-patient (r=0.770), moderate positive correlation between physician-parent (r=0.456) and physician-patient (r=0.512). There was also statistically positive correlation between the patient and parent pain score (r=0.857). Conclusions: We assessed the main clinical and laboratory features, and the disease activity status of the Turkish patients with childhood chronic arthritis. We evaluated the diagnoses and the subtype distributions according to ILAR classification. Disclosure of Interest: None declared